Dynamic Capabilities and an ESG Strategy for Sustainable Management Performance - Liang, Yi; Lee, Min Jae; Jung, Jin Sup (Frontiers in Psychology, 2022)
This research explores the dynamic capabilities required for firms to implement environmental, social, and governance (ESG) strategies, and investigates sustainable management performance that can be created based on them. By using dynamic capabilities theory, we integrate sustainable management and the ESG literature to suggest a research model and identify the factors that act as the catalysts achieving sustainability. The data used for the analysis were collected from 78 firms listed on the Korea Exchange (KRX) with assets totaling more than 2 trillion Korean won. In this study, the partial least squares structural equation model (PLS-SEM) is applied. We found that absorptive capability and adaptive capability significantly affect sustainable management performance through implementation of the ESG strategy as a mediating variable. In particular, a firm’s implementation of an ESG strategy is a significant determinant that impacts sustainable management performance. We also believe our model contributes to the current knowledge by filling several research gaps, and our findings offer valuable and practical implications not only for achieving sustainable growth but also for creation of competitive advantage.